RICKSHAW WRITINGS – A REAL MIRROR TO PAKISTANI SOCIETY - Muhammad Siddique; Manvender Kaur Sarjit Singh (Proceedings of The ICECRS, 2016)
Cultural diversity can be seen in many forms. One specific area of interest would be the use of language in expressing opinions related to many aspects of a society. This particular study reports on the use of culturally influenced language, in order to express opinions as reflected on auto rickshaws in Lahore, Pakistan. Data was gathered by observations while travelling to various areas in Lahore, Pakistan. The qualitative analysis of the written discourse showed various aspects of life of the Lahorites, through different modes as were reflected by the writings on the rickshaws plying throughout the town.